Social Work Practice and Communication for Girl Survivors of Sexual Violence: A Social Rehabilitation Perspective in Indonesia - Bambang Rustanto; Ayi Haryani; Tuti Kartika; Pribowo; Susilawati; Dwi Yuliani; Aryohaji Istyawan (INJECT (Interdisciplinary Journal of Communication), 2026)
Sexual violence against girls constitutes a serious violation of human rights, with profound physical, psychological, and social consequences that require comprehensive and sustained responses. Within this context, such violence is closely linked to gendered power relations and vulnerabilities shaping girl’s experiences and recovery processes. This study aims to examine social work practice and communication in social rehabilitation for girl survivors of sexual violence at a Handayani Jakarta Service Center in Indonesia. A qualitative phenomenological approach was employed, with data collected through in-depth interviews, observations, and document analysis involving five purposively selected informants, consisting of three social workers, one acting head of the center, and one administrative head; data were analyzed through reduction, display, and conclusion drawing. The findings indicate that social rehabilitation is implemented through stages including assessment, service planning, interventions across family, community, and residential settings, as well as monitoring and post-service support, with social workers performing on practice and communication within a survivor-centered approach. The study concludes that strengthening professional capacity, cross-sector coordination, and inclusive strategies is essential to support the sustainable recovery of girl survivors.